2020
DOI: 10.1186/s13104-020-05287-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and economical drug resistance profiling with Nanopore MinION for clinical specimens with low bacillary burden of Mycobacterium tuberculosis

Abstract: Objective We designed and tested a Nanopore sequencing panel for direct tuberculosis drug resistance profiling. The panel targeted 10 resistance-associated loci. We assessed the feasibility of amplifying and sequencing these loci from 23 clinical specimens with low bacillary burden. Results At least 8 loci were successfully amplified from the majority for predicting first- and second-line drug resistance (14/23, 60.87%), and the 12 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Other studies have also shown 100% of agreement in the prediction of drug-resistance-associated variants between Illumina and MinION Nanopore when variants detected by MinION at an allele frequency below 0.4 are excluded from the analysis [50,51]. Similarly, two recent studies showed complete concordance between both sequencing platforms when applied a threshold 0.8 to call fixed variants [52,53]. Accurate identification of low-frequency variants is relevant for clinical management [11,54] especially for drugs such as fluoroquinolones, for which frequencies ranging from 14-38 % have been reported [55].…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have also shown 100% of agreement in the prediction of drug-resistance-associated variants between Illumina and MinION Nanopore when variants detected by MinION at an allele frequency below 0.4 are excluded from the analysis [50,51]. Similarly, two recent studies showed complete concordance between both sequencing platforms when applied a threshold 0.8 to call fixed variants [52,53]. Accurate identification of low-frequency variants is relevant for clinical management [11,54] especially for drugs such as fluoroquinolones, for which frequencies ranging from 14-38 % have been reported [55].…”
Section: Discussionmentioning
confidence: 86%
“…We identified 58 articles of which 12 were eligible. Five articles focused on whole-genome sequencing (WGS) ( 8 , 12 , 21 23 ), three on targeted sequencing ( Table 1 ) ( 11 , 24 , 25 ), and four on software development for long-read ONT sequencing data with applications for M. tuberculosis ( Table 2 ) ( 16 , 18 , 19 , 26 ).…”
Section: Ont Sequencing For M Tuberculosis Researc...mentioning
confidence: 99%
“…Three studies that assessed ONT sequencing for targeted sequencing of drug resistance loci were all published in 2020 ( 11 , 24 , 25 ). Tafess et al ( 24 ) and Chan et al ( 25 ) used custom-made panels of 19 and 10 drug resistance-associated loci, respectively.…”
Section: Ont Sequencing For M Tuberculosis Researc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among widely applied platforms, the ONT platform is suitable for sequencing the GC-rich or repetitive proline-glutamate regions within the MTB genome, which might be omitted in results of short-read sequencing [ 14 ]. Moreover, the increased accuracy of the ONT platform of assembling a precise MTB genome is achieved with a higher reading depth compared to that of the Illumina platform [ 7 , 15 ]. The MinION quality score does not equate to the same Phred score, a mean quality score of 20.07 regarding the per base quality score of MinION sequencing were assessed using the CLC genomics workbench in this study.…”
Section: Discussionmentioning
confidence: 99%